Pain Behavioural Response to Acoustic and Light Environmental Changes in Very Preterm Infants - Audrey Marchal; Meggane Melchior; André Dufour; Pierrick Poisbeau; Claire Zores; Pierre Kuhn (MDPI AG, 2021)
Noise and high light illumination in the neonatal intensive care unit (NICU) are recognized as stressors that could alter the well-being and development of vulnerable preterm infants. This prospective observational study evaluated the pain behaviours of very preterm infants (VPIs) to sound peaks (SPs) and light levels variations (LLVs) in the NICU. We measured spontaneously occurring SPs and LLVs in the incubators of 26 VPIs over 10 h. Their behavioural responses were analysed through video recordings using the "Douleur Aigue du Nouveau-né" (DAN) scale. We compared the maximum DAN scores before and after environmental stimuli and the percentage of VPIs with a score ≥ 3 according to the type of stimuli. A total of 591 SPs and 278 LLVs were analysed. SPs of 5 to 15 dBA and LLVs significantly increased the maximum DAN scores compared to baseline. The occurrence of DAN scores ≥ 3 increased with both stressors, with a total of 16% of SPs and 8% of LLVs leading to quantifiable pain behaviour. Altogether, this study shows that VPIs are sensitive to SPs and LLVs, with a slighter higher sensitivity to SPs. The mechanisms leading to pain behaviours induced by noise and light changes should be evaluated further in the context of VPIs brain development. Our results provide further arguments to optimize the NICU sensory environment of neonatal units and to adapt it to the expectations and sensory abilities of VPIs.